(untitled) (Menara Perkebunan, 2016)
Summary Attempts to improve productivity of cacao plantations lead us to study the molecular mechanism of flowering. In the model species Arabidopsis thaliana as well as some other species, LEAFY is a central regulatory gene for the transition of shoot apical meristems to flowering meristems. Different from that of Arabidopsis, cacao inflorescence is a cauliflorous type, by which flowers can develop repeatedly from the same flower cushion on the trunk. In this research, a LEAFY homolog was isolated from active flower cushion with RT-PCR using a pair of DNA primer specifically designed to isolate its complete cds. Gel electrophoresis examination indicated the presence of a 1.2 kb amplicon. Purified from the gel, this DNA fragment was cloned into competent cells of E. coli XL1 Blue using pGEM-T Easy cloning vector at an orientation according to the T7 promoter of the plasmid. Sequence analysis using BLASTX, showed that the amplicon was LEAFY (LFY) homolog. Alignment analysis using Clustal W indicated that the cTcLFY highly homologous to those from other perennial crops such as citrus, grape, apple and poplar. The highest homology (conserved region) was found in the C terminal of the encoded proteins. Ringkasan Usaha untuk meningkatkan produktivitas perkebunan kakao telah mendorong penelitian molekuler tentang mekanisme pembungaan kakao. Pada tanaman model Arabidopsis thaliana dan lainnya, LEAFY merupakan gen kunci dalam transisi meristem tunas jadi meristem bunga. Berbeda dengan sistem pada Arabidopsis, pembungaan kakao termasuk tipe cauliflorous, bunga dapat muncul dari bantalan bunga yang sama sepanjang tahun. Dalam penelitian ini homolog LFY diisolasi dari bantalan bunga aktif menggunakan RT-PCR dengan sepasang primer spesifik yang dirancang berdasarkan sekuen DNA di kedua ujung gen tersebut. Pemeriksaan gel elektroforesis menunjukkan adanya amplikon tunggal berukuran 1,2 kb. Setelah dimurnikan dari gel, amplikon dapat diklon ke dalam sel kompeten E. coli galur XL1 Blue menggunakan vektor pGEM-T Easy dengan orientasi yang sesuai dengan promoter T7 dari vektor. Analisis BLASTX sekuen DNA membuktikan bahwa amplikon tersebut adalah homolog dari gen LEAFY. Analisis penjajaran dengan mengguna- kan ClustalW menunjukkan bahwa gen cTcLFY tersebut memiliki homologi yang tinggi dengan gen sejenis dari tanaman keras lainnya seperti tanaman jeruk, anggur, apel dan poplar. Homologi tertinggi (daerah terkonservasi) terdapat pada ujung (terminal) C dari protein yang disandinya.